D-Cycloserine: An Evolving Role in Learning and Neuroplasticity in Schizophrenia - Goff, Donald C. (Oxford University Press, 2012)
As a partial agonist at the glycine site of the NMDA receptor, D-cycloserine (DCS) has been viewed as lacking potency to fully test the NMDA receptor hypofunction theory of schizophrenia. However, findings of full agonist activity at a subset of NMDA receptors that may have particular relevance to schizophrenia, plus a growing body of evidence demonstrating enhancement of learning and neuroplasticity in animal models, suggest novel therapeutic strategies with DCS in schizophrenia. Preliminary studies with once-weekly administration have supported this potential new role for DCS in schizophrenia by demonstrating benefit for negative symptoms, memory consolidation, and facilitation of cognitive behavioral therapy for delusions.